Responses of non-eye movement central vestibular neurons to sinusoidal horizontal translation in compensated macaques after unilateral labyrinthectomy - Newlands, Shawn D. (American Physiological Society, 2014)
After vestibular labyrinth injury, behavioral deficits partially recover through the process of vestibular compensation. The present study was performed to improve our understanding of the physiology of the macaque vestibular system in the compensated state (>7 wk) after unilateral labyrinthectomy (UL). Three groups of vestibular nucleus neurons were included: pre-UL control neurons, neurons ipsilateral to the lesion, and neurons contralateral to the lesion. The firing responses of neurons sensitive to linear acceleration in the horizontal plane were recorded during sinusoidal horizontal translation directed along six different orientations (30° apart) at 0.5 Hz and 0.2 g peak acceleration (196 cm/s(2)). This data defined the vector of best response for each neuron in the horizontal plane, along which sensitivity, symmetry, detection threshold, and variability of firing were determined. Additionally, the responses of the same cells to translation over a series of frequencies (0.25–5.0 Hz) either in the interaural or naso-occipital orientation were obtained to define the frequency response characteristics in each group. We found a decrease in sensitivity, increase in threshold, and alteration in orientation of best responses in the vestibular nuclei after UL. Additionally, the phase relationship of the best neural response to translational stimulation changed with UL. The symmetry of individual neuron responses in the excitatory and inhibitory directions was unchanged by UL. Bilateral central utricular neurons still demonstrated two-dimension tuning after UL, consistent with spatio-temporal convergence from a single vestibular end-organ. These neuronal data correlate with known behavioral deficits after unilateral vestibular compromise.